2019
DOI: 10.1002/eat.23001
|View full text |Cite
|
Sign up to set email alerts
|

Transactions among thinness expectancies, depression, and binge eating in the prediction of adolescent weight control behaviors

Abstract: Objective: Binge eating, the transdiagnostic risk associated with depression, and the eating disorder-specific risk associated with expectancies for reinforcement from thinness have been identified as risk factors for the development of weight control behaviors. The purpose of this study was to examine if these risk factors transact to further predict risk in youth.Method: Binge eating, depressive symptoms, thinness expectancies, and weight control behaviors were assessed in 1,758 adolescents three times durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Studies have highlighted the significance of exploring these relationships among children and adolescents, as this developmental period is a critical stage for learning healthy and unhealthy habits and behaviors (Klomek et al, 2007;Lewinsohn & Essau, 2002;Cicchetti & Toth, 1998). For example, researchers have found that depressive symptoms are associated with maladaptive behaviors, including disordered eating, alcohol use, and tobacco use (Fluharty et al, 2017;Johannessen et al, 2017;Ortiz et al, 2019).…”
mentioning
confidence: 99%
“…Studies have highlighted the significance of exploring these relationships among children and adolescents, as this developmental period is a critical stage for learning healthy and unhealthy habits and behaviors (Klomek et al, 2007;Lewinsohn & Essau, 2002;Cicchetti & Toth, 1998). For example, researchers have found that depressive symptoms are associated with maladaptive behaviors, including disordered eating, alcohol use, and tobacco use (Fluharty et al, 2017;Johannessen et al, 2017;Ortiz et al, 2019).…”
mentioning
confidence: 99%